Fluid shear stress activates YAP to promote epithelial–mesenchymal transition in hepatocellular carcinoma. Issue 11 (2nd August 2021) - Yu, Hongchi; He, Jia; Su, Guanyue; Wang, Yuelong; Fang, Fei; Yang, Wenxing; Gu, Kaiyun; Fu, Naiyang; Wang, Yunbing; Shen, Yang; Liu, Xiaoheng
Abstract : Epithelial–mesenchymal transition (EMT) mediated by fluid shear stress (FSS) in the tumor microenvironment plays an important role in driving metastasis of the malignant tumor. As a mechanotransducer, Yes‐associated protein (YAP) is known to translocate into the nucleus to initiate transcription of genes involved in cell proliferation upon extracellular biophysical stimuli. Here, we showed that FSS facilitated cytoskeleton rearrangement in hepatocellular carcinoma cells, which led to the release of YAP from its binding partner, integrin β subunit, in the cytomembrane. Moreover, we found that upregulation of guanine nucleotide exchange factor (GEF)‐H1, a microtubule‐associated Rho GEF, is a critical step in the FSS‐induced translocation of YAP. Nuclear YAP activated the expression of the EMT‐regulating transcription factor SNAI1, but suppressed the expression of N6‐methyladenosine (m 6 A) modulators; together, this promoted the expression of EMT‐related genes. We also observed that FSS‐treated HepG2 cells showed markedly increased tumorigenesis and metastasis in vivo . Collectively, our findings unravel the underlying molecular processes by which FSS induces translocation of YAP from the cytomembrane to the nucleus, contributes to EMT and enhances metastasis in hepatocellular carcinoma. Abstract : Here, we describe the underlying mechanism by which fluid shear stress (FSS) induces epithelial–mesenchymal transition (EMT) and enhances metastasis in hepatocellular carcinoma. Upon FSS, Yes‐associated protein (YAP) was released from its membrane binding partner integrin β subunits. Upregulation of GEF‐H1 promoted FSS‐induced nuclear translocation of YAP, which in turn regulated EMT‐related gene expression through SNAI1 and m 6 A modulators.